Cost Estimates of Producing Sapodilla in South Florida, 2017 - Fredy H. Ballen; Aditya Singh; Edward A. Evans; Jonathan H. Crane (EDIS)
This 6-page fact sheet written by Edward A. Evans, Fredy H. Ballen, Aditya Singh, and Jonathan H. Crane and published by the UF/IFAS Food and Resource Economics Department provides an estimate of the costs and returns associated with an established sapodilla orchard in south Florida. The information presented is based on a wide range of production practices collected through field interviews with growers and industry specialists and is intended as a guide to estimate the financial aspects of operating an established sapodilla grove. Please note that sapodilla has been assessed by the UF/IFAS Invasive Plants Working Group as potentially invasive in south and central Florida. It should not be planted in home landscapes or in groves near natural areas. Sapodilla plantings must be fenced, and the fruit must be moved in covered vehicles to prevent fruit being eaten by wildlife and the plant from infesting areas outside the grove. http://edis.ifas.ufl.edu/fe1015